Launching IDeA state early career clinician-scientists with mentored just-in-time grant-writing support - Danielle R. Hatchimonji; Melissa A. Alderfer; Erin L. Riegel; Robert E. Akins (Journal of Clinical and Translational Science, 2023)
Institutional Development Award (IDeA) programs build research infrastructure in regions with historically low access to NIH funds. The Mentored Research Development Award (MRDA), a professional development program embedded in our IDeA-funded center, provides junior investigators with mentorship and effort offset to write a grant. We evaluated outcomes from the first eight years (2013–2021; N = 55) using administrative records, publicly available data, and a self-report survey (n = 46, 84% response rate). Fifteen MRDA recipients (27%) went on to receive NIH funding. Providing just-in-time grant-writing support may launch early career clinician-scientists in an IDeA state context.